Analysis of Transferred Potentials on Substation Fences - Erika Stracqualursi; Rodolfo Araneo; Massimo Mitolo (IEEE Open Journal of Industry Applications)
Grounding systems play a critical role in ensuring the safety and reliability of power systems, particularly in substations, where public access poses a significant risk. This article presents a computational study of grounding configurations for substation fences, based on guidelines from the IEEE Std 80-2000. A specialized code was developed and tested to simulate various grounding scenarios, including cases where the fence is connected to or isolated from the substation's grounding grid. The study examines key parameters, such as touch and surface potentials under fault conditions. Prospective and simulation results on five distinct fence grounding setups are presented. The article highlights the effectiveness of the developed code in accurately predicting hazardous conditions, providing valuable insights for optimizing substation grounding designs.